Gender Performativity and Non-Binary Identities on Social Media: An Analysis of Chris Derek's Instagram Content in Judith Butler's Theory Framework - Julianto, Edi Nurwahyu; Seran, Alexander (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study investigates how non-binary identity is constructed and performatively represented through the social media platform Instagram, using Indonesian public figure Chris Derek as a case study. Employing Judith Butler’s theory of gender performativity within the critical theory tradition, the research explores three key dimensions of Instagram content: performative visuals, performative narratives, and digital symbols. Ten posts with the highest engagement containing non-binary identity markers—visually, textually, or symbolically—were purposively selected and analyzed. The findings reveal that Chris Derek’s gender performance is a complex negotiation between personal identity expression, professional aesthetic strategy, and participation in digital queer communities. Feminine visual representations and hashtags such as #nonbinarymodel and #pride? emerge as core strategies of affirmation. The study concludes that social media, particularly Instagram, functions not only as a platform for self-display but also as a symbolic political arena where gender is negotiated, reproduced, and contested. This research contributes to the expansion of queer and digital communication studies in the Indonesian context, where such explorations remain limited.